Design of Bessel low-pass filter using DGS for RF/microwave applications. Issue 9 (1st September 2016) - Kumar, Ashwani; Verma, A.K.
ABSTRACT: A synthesis method to design a defected ground structures (DGS)-based Bessel low-pass filter (LPF) using a triangular and an open-square (OS)-type DGS is reported. For the five-pole Bessel LPF at f c  = 2.5 GHz, we get 10.6 dB/GHz selectivity using the triangular DGS; while the OS-type DGS provides 39 dB/GHz selectivity. For these two filters, the 10 dB impedance matching BW is 76% and 84%, respectively. It is a much wider BW that is obtained for a lumped element Bessel LPF. The maximum group delay (GD) variation within the pass band is 25pS and 28pS, respectively. The 20 dB rejection BW can be increased from 5.8 GHz to 18.8 GHz with increase in the order of filter from 5 to 11. We have also presented the design of a compact five-pole DGS-based elliptic filter with selectivity 38.2 dB/GHz and 17.8 dB return loss. Results on the DGS-based elliptic filter, Butterworth and Chebyshev filters are also presented. The experimental results are compared against the recently reported LPFs. Our reported filters perform better with respect to selectivity and group delay variation. The flatter GD and high selectivity, along with a wide 10 dB impedance matching BW, make the DGS Bessel filter a candidate for high-speed data communication, front end of a wideband communication system and efficiency improvement of a power amplifier.